El diseño de una base de datos para una representación de las fuentes históricas valencianas. - HERNÁNDEZ, CELIO (Scripta)
In the field of Digital Humanities, the development of databases for efficient access and organisation of their content, especially regarding historical sources, is crucial. Both «memory institutions» and university projects have specialised for decades in the creation and improvement of these databases, with varying degrees of complexity, to facilitate the work of the scientific community and, occasionally, to centralise information scattered across the web. This is the case with the VaHiFo project (Valentiae Historici Fontes) from UV/IIFV, which, to gather references on Valencian historical sources, has embarked on their identification and registration, as well as the creation of a database to organise and manage them. The aim of this article is to demonstrate the design process of this tool, focusing on aspects such as ease of use, durability, and evolutionary capacity. Additionally, it offers a methodology that conceptualises the unified description of Valencian historical sources, encompassing different genres and various material or edition types, whilst also emphasising the relationship between the testimonies of their tradition.